Assessment of technical skills in young soccer goalkeepers: Reliability and validity of two goalkeeper-specific tests - Rebelo-Goncalves, R.; Figueiredo, A. J.; Coelho e Silva, M. J.; Tessitore, A. (Journal of Sports Science & Medicine, 2016)
The purpose of this study was to evaluate the reproducibility and validity of two new tests designed to examine goalkeeper-specific technique. Twenty-six goalkeepers (14.49 ± 2.52 years old) completed two trial sessions, each separated by one week, to evaluate the reproducibility of the Sprint-Keeper Test (S-Keeper) and the Lateral Shuffle-Keeper Test (LS-Keeper). Construct validity was assessed among forty goalkeepers (14.49 ± 1.71 years old) by competitive level (elite versus non-elite), after controlling for chronological age. All participants were examined in vertical jump (CMJ and CMJ-free arms), acceleration (5-m and 10-m sprint) and goalkeeper-specific technique. The S-Keeper requires the goalkeeper to accelerate during 3 m and dive over a stationary ball after performing a change of direction in a total distance of 10 m. The LS-Keeper involves three changes of direction and a diving save over a stationary ball, in a total distance of 12.55 m. Performance was respectively measured as total time for the right and left sides in each protocol. Bivariate correlations between repeated measures were high and significant (r = 0.835 - 0.912). Test-retest results for the S-Keeper and LS-Keeper showed good reliability (reliability coefficients > 0.88, intra-class correlation coefficient > 0.908 and coefficients of variation < 4.37%), even though participants tended to improve performance when diving to their right side (p < 0.05). Both tests were able to detect significant differences between elite and non-elite goalkeepers, particularly to the left side (p < 0.05). These findings suggest that the S-Keeper and LS-Keeper are reliable and valid tests for assessing goalkeeper-specific technique. Both protocols can be used as a practical tool to provide relevant information about the influence of several components of performance in the overall execution of a diving save, particularly movement patterns, take-off movements and possible asymmetries.